Road traffic noise, air pollution and incident cardiovascular disease: A joint analysis of the HUNT, EPIC-Oxford and UK Biobank cohorts. (May 2018) - Cai, Yutong; Hodgson, Susan; Blangiardo, Marta; Gulliver, John; Morley, David; Fecht, Daniela; Vienneau, Danielle; de Hoogh, Kees; Key, Tim; Hveem, Kristian; Elliott, Paul; Hansell, Anna L.
Abstract: Background: This study aimed to investigate the effects of long-term exposure to road traffic noise and air pollution on incident cardiovascular disease (CVD) in three large cohorts: HUNT, EPIC-Oxford and UK Biobank. Methods: In pooled complete-case sample of the three cohorts from Norway and the United Kingdom (N = 355, 732), 21, 081 incident all CVD cases including 5259 ischemic heart disease (IHD) and 2871 cerebrovascular cases were ascertained between baseline (1993–2010) and end of follow-up (2008–2013) through medical record linkage. Annual mean 24-hour weighted road traffic noise (Lden) and air pollution (particulate matter with aerodynamic diameter ≤ 10 μm [PM10], ≤2.5 μm [PM2.5] and nitrogen dioxide [NO2]) exposure at baseline address was modelled using a simplified version of the Common Noise Assessment Methods in Europe (CNOSSOS-EU) and European-wide Land Use Regression models. Individual-level covariate data were harmonised and physically pooled across the three cohorts. Analysis was via Cox proportional hazard model with mutual adjustments for both noise and air pollution and potential confounders. Results: No significant associations were found between annual mean Lden and incident CVD, IHD or cerebrovascular disease in the overall population except that the association with incident IHD was significant among current-smokers. In the fully adjusted models including adjustment for Lden, an interquartile range (IQR) higher PM10 (4.1 μg/m3) or PM2.5 (1.4 μg/m3) was associated with a 5.8% (95%CI: 2.5%–9.3%) and 3.7% (95%CI: 0.2%–7.4%) higher risk for all incident CVD respectively. No significant associations were found between NO2 and any of the CVD outcomes. Conclusions: We found suggestive evidence of a possible association between road traffic noise and incident IHD, consistent with current literature. Long-term particulate air pollution exposure, even at concentrations below current European air quality standards, was significantly associated with incident CVD. Highlights: An individual-level study of 355, 732 adults from three population-based cohorts Association between Lden and incident ischemic heart disease was found in smokers. Null associations were found between road traffic noise and incident stroke. PM10 was associated with all incident cardiovascular disease, adjusted for noise.